Effectiveness and acceptability of the unified protocol for the transdiagnostic treatment of emotional disorders in people with long COVID-19: Study protocol for a randomized controlled trial - Verónica Martínez-Borba; Andrés E. Rodríguez-Márquez; Sara Garcés-Arilla; Óscar Peris-Baquero; María Vicenta Navarro-Haro; Esther del Corral-Beamonte; Jorge Osma (PLoS ONE, 2026)
Background Long COVID-19 is a medical condition associated with persistent physical, cognitive, and emotional symptoms. Despite its significant impact, there are still few psychological interventions—especially with transdiagnostic approaches— that have been rigorously tested in this population. The aim of the present protocol is to describe a randomized controlled trial to examine the effectiveness and acceptability of the online, group-delivered Unified Protocol (UP) for improving emotional, and cognitive outcomes in adults with long COVID-19. We expect greater improvements in emotional and cognitive outcomes for the UP group compared to controls. Additionally, exploratory analyses will assess changes in neurocognitive performance and hair cortisol/cortisone levels as potential correlates of treatment response. Methods 90 individuals diagnosed with long COVID-19 will be randomized to an experimental group or a waiting-list control group (1:1 ratio). Participants in the experimental group will receive the UP across 12 online group sessions. Longitudinal assessments (pre-treatment, post-treatment and 3, 6 and 12 months follow-ups) will include psychological (e.g., anxiety and depressive symptoms) and cognitive outcomes (e.g., memory failures). Participants in the experimental group will also complete neuropsychological tests and will provide hair samples for the assessment of cortisol/cortisone levels. Data analyses Baseline characteristics will be described using descriptive statistics, and linear mixed-effects models will evaluate the effects of time, group, and their interaction on psychological and cognitive outcomes. Neuropsychological performance and hair cortisol levels will be analyzed over time in the experimental group. Associations between cortisol and psychological or cognitive measures will be explored through correlational analyses. Conclusions We expect positive outcomes after the intervention in acceptability and in emotional symptoms and cognitive complaints in individuals living with long COVID-19, the maintenance of the benefits in all follow-ups, and statistically significant changes in favor of the UP condition in comparison with the waiting-list control group. If effective, the UP could provide an accessible and evidence-based psychological treatment for this population, improving the quality of healthcare to individuals with long COVID-19. Trial registration clinicatrials.gov (registration identifier: NCT06928480 ; May 22, 2025).